STIMULASI TUMBUH KEMBANG ANAK - Sri Yenawati (Psympathic : Jurnal Ilmiah Psikologi, 2010)
Children, like adults are also have their own problems in life. Nowadays, we also know that lacks of self confidence not just for adult only, children are also have the same problem. It is also encouraged by their undeveloped ability both mentally and physically. Independency is also one of many problems that must be faced by children especially children with mental disorder or mental retardation. This phenomena then become a basis for this research—that is emphasizes on children development stimulation. It was also considered that pre-natal condition is also has influence over children’s  development after they born. This paper is then pre-describe developmental stage of children at their golden age, with developmental tasks and crisis that come along within every stages. Stimulation to encourage children’s development would also be discussed in this  paper with hopes that many people could then take any profit from this paper and optimizing their effort in raising and teaching their children.